Implementasi Peran Kurator dalam Proses Kepailitan Pasca PKPU Berdasarkan Undang Undang Kepailitan No 37 Tahun 2004 - Doni Margipson Sitohang; Roida Nababan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This research examines the implementation of the curator’s role in the bankruptcy process following the Postponement of Debt Payment Obligations (PKPU) based on Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The main objective of this study is to analyze the role, authority, and challenges faced by curators in carrying out their duties in accordance with Indonesia’s positive legal framework. This research employs a normative juridical approach combined with an empirical juridical approach, incorporating a review of legal literature, court rulings, and statutory regulations, as well as interviews with curators and supervising judges in commercial courts. The findings reveal that curators play a central role as administrators and liquidators of bankrupt estates, with the authority to inventory, secure, manage, and liquidate the debtor’s assets to protect creditors’ interests. Pursuant to Law Number 37 of 2004, curators are also responsible for overseeing the bankruptcy process, preparing reports, and ensuring that the distribution of liquidation proceeds is conducted transparently and equitably. However, the implementation of this role often faces obstacles such as limited curator competence and resources, external interference, the complexity of bankruptcy laws, and inadequate judicial supervision. This study emphasizes the importance of legal reform, professional capacity building, and the adoption of digital technology to enhance the effectiveness of Indonesia’s bankruptcy system. A professional, accountable, and integrity-driven curator is essential to achieving the fundamental objectives of bankruptcy law—ensuring fair, efficient, and transparent debt settlement for all parties involved.